The Kv7 Channel and Cardiovascular Risk Factors - Fosmo, Andreas L.; Skraastad, Øyvind B. (Frontiers in Cardiovascular Medicine, 2017)
Potassium channels play a pivotal role in the regulation of excitability in cells such as neurons, cardiac myocytes, and vascular smooth muscle cells. The KCNQ (Kv7) family of voltage-activated K+ channels hyperpolarizes the cell and stabilizes the membrane potential. Here, we outline how Kv7 channel activity may contribute to the development of the cardiovascular risk factors such as hypertension, diabetes, and obesity. Questions and hypotheses regarding previous and future research have been raised. Alterations in the Kv7 channel may contribute to the development of cardiovascular disease (CVD). Pharmacological modification of Kv7 channels may represent a possible treatment for CVD in the future.